2013
DOI: 10.1016/j.cell.2013.08.004
|View full text |Cite
|
Sign up to set email alerts
|

The CRTC1-SIK1 Pathway Regulates Entrainment of the Circadian Clock

Abstract: SummaryRetinal photoreceptors entrain the circadian system to the solar day. This photic resetting involves cAMP response element binding protein (CREB)-mediated upregulation of Per genes within individual cells of the suprachiasmatic nuclei (SCN). Our detailed understanding of this pathway is poor, and it remains unclear why entrainment to a new time zone takes several days. By analyzing the light-regulated transcriptome of the SCN, we have identified a key role for salt inducible kinase 1 (SIK1) and CREB-reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
184
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(192 citation statements)
references
References 74 publications
5
184
2
1
Order By: Relevance
“…4B). The induction of SIK1 expression by cAMP signaling was previously shown in hepatocytes and neuronal cells, suggesting that the similar mechanism is also conserved in b-cells (13,15). These data suggest that SIK1 could potentially be involved in the feedback inhibitory mechanism in reducing cAMPdependent signaling at the later point after initial burst.…”
Section: Sik1-dependent Phosphorylation and Activation Of Pde4d Reducmentioning
confidence: 59%
See 1 more Smart Citation
“…4B). The induction of SIK1 expression by cAMP signaling was previously shown in hepatocytes and neuronal cells, suggesting that the similar mechanism is also conserved in b-cells (13,15). These data suggest that SIK1 could potentially be involved in the feedback inhibitory mechanism in reducing cAMPdependent signaling at the later point after initial burst.…”
Section: Sik1-dependent Phosphorylation and Activation Of Pde4d Reducmentioning
confidence: 59%
“…In addition to its role as an inhibitory kinase for CRTCs and subsequent gluconeogenesis in hepatocytes, SIK1 is also shown to be involved in the regulation of myogenesis by direct phosphorylation of histone deacetylase 5 in muscle cells and in the regulation of lipogenesis in the liver by conferring an inhibitory phosphorylation mark on SREBP-1c, showing the importance of SIK1 as a regulator of metabolic pathways in insulin-sensitive tissues (12)(13)(14). In particular, as a direct target gene of CREB/CRTCs, SIK1 has been shown to be involved in the negative-feedback loop that would terminate cAMP-dependent transcriptional responses (12,13,15).…”
mentioning
confidence: 99%
“…DNA microarray studies have shown that several hundred genes are down-regulated and 100 genes are acutely up-regulated by a delaying light pulse (Jagannath et al 2013). The latter group included the coactivator of CREB, CRTC1 (Sakamoto et al 2013), and salt inducible kinase 1 (Sik1).…”
Section: Regulating the Scn Circadian Clockworkmentioning
confidence: 99%
“…In addition, NE also regulates the phosphorylation status and cellular localization of CRTC1 and CRTC2 (Kanyo et al, 2011;McTague et al, 2012McTague et al, , 2013. Together, this suggests that SIK1 may repress the transcription of Aanat in the rat pineal gland by regulating the phosphorylation and distribution of CRTCs as reported in other tissues (Dentin et al, 2007(Dentin et al, , 2008Jagannath et al, 2013;Koo et al, 2005;Liu et al, 2010Liu et al, , 2012Sakamoto et al, 2013;Takemori et al, 2007). In the present study, the role of SIK1 was investigated by determining the effect of manipulating its level on the phosphorylation and distribution of CRTC1 and CRTC2.…”
Section: Discussionmentioning
confidence: 76%
“…The SIK1/CRTCs signalling pathway, has been shown to be involved in the control of glucose metabolism in the liver, corticotropin-releasing hormone transcription in the hypothalamic neurons and the circadian clock entrainment in the suprachiasmatic nuclei (Dentin et al, 2007(Dentin et al, , 2008Jagannath et al, 2013;Koo et al, 2005;Liu et al, 2010Liu et al, , 2012Sakamoto et al, 2013). In the rat pineal gland, we have established that the expression of SIK1 can be stimulated by NE and that SIK1 can function as a repressor of the NE-stimulated Aanat transcription (Kanyo et al, 2009).…”
Section: Discussionmentioning
confidence: 99%